A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus - Díaz, René Barba; Zaragoza, Juan A.; Iborra, Germán López (Zootaxa, 2018)
A new troglobitic species of the genus Antillobisium is described from Sancti Spiritus province, Cuba. Antillobisium tomasi n. sp. is the third known species of the genus and is well characterized by its large size and extremely slender appendages. Biogeographical and ecological considerations on the genus are given.